The ANDES Underground Laboratory Project - Civitarese, Enrique Osvaldo (2015)
This talk will be devoted to the presentation of the ANDES underground laboratory project. We shall talk about the motivations, prospects and design of this facility, which will be the first of its type in the southern hemisphere. The physics involved, as well as other potential applications to biology, geology and material sciences, are discussed.